Shape the Enterprise, Shape the Life: Strategy of Living Life in Refuge as an Ethnic Entrepreneur in Light of Immaterial Labor - Alves Scherer, Laura; Amaral Prestes, Vanessa; Iochins Grisci, Carmem Lígia (Organizações & Sociedade, 2022)
This article aims to present and analyze the strategy for living life of Syrian refugees, examining the ethnic enterprise in light of the notion of immaterial labor. A qualitative and exploratory study was conducted in the city of Porto Alegre (Brazil), based on a corpus of research whose thematic focus was ethnicity in the food-sector enterprises of Syrian refugees. The data were accessed by means of newspaper reports, visits to the enterprises, the consumption of products, narrative interviews, and direct observation with photographic and field diary records. The participants were Syrian refugees interconnected through family ties and a common origin who share two enterprises – an ethnic snack bar and confectionery. The analysis resulted in three axes: (a) routes and obstacles in refuge; (b) immaterial labor in the ethnic enterprise; and (c) being an ethnic entrepreneur as a strategy for living life in refuge. It is highlighted that the metaphorical models of wanderer and player help to illustrate the production of subjectivity outlining the ethnic entrepreneur as a strategy for living life as a refugee operationalized by immaterial labor. These conclusions provide an analytical perspective on the subjectivity for ethnic enterprises by showing that the ethnic entrepreneur in correspondence with the self-entrepreneur in immaterial labor operates in the sense of producing/composing/affirming the strategy for living life in refuge. Thus, by shaping the enterprise, it shapes the life.